POLA SEGREGASI PEMUKIMAN MASYARAKAT PEKANBARU - Sihotang, Rio Putra; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducteds in pekanbaru city, with comparison about five area, the goals that reached are : (a) to study the pattern district segregation of society pekanbaru, (b) to understand the impact that caused by district segregation,. The theory that used in this research are the social contruction, AGIL concept, and system of town. According to the population, a given 80 partisipant as the sampel of the research that used quantitative descriptive method and sampling cluster technique.According to the research has got a conclusion that, there are a similarity and dissimilarity in figuration of district segregation, the greatest factor which influence made of district segregation are economy and job sector, intervention and inregration. The effect which caused of district segregation existence, viewed by fungtional perspective, and find the result, that district segregation make affect the value of society integration and consolidate relation and interaction society inside the district range.Key words : Pattern, District Segregation, Integration